Developing a Bilingual Guidebook as the Promotional Media for Desa Wisata Sendang Duwur Lamongan - Azzahra Firdausy Arifani (Jurnal Linguistik Terapan, 2025)
Sendang Duwur Tourism Village is a tourism village in Lamongan, East Java that offers spiritual and cultural tourism destinations. According to the visitor’s statistic in 2022 to 2023 from the head of Sendang Duwur Village, approximately 15% of international tourists visited this village. An issue arose because there was no medium to promote the tourism potential in Sendang Duwur Village. Therefore, to address the need of village government, the researcher decided to develop a bilingual guidebook with complete information about Sendang Duwur Village. The research was used Design and Development Research or DDR by (Richey & Klein, 2005), and adopted ADDIE model: Analysis, Design, Development, Implementation, and Evaluation for the research procedure. The data collection was obtained from online research, observation, interview, and questionnaires. The purpose of this research is to develop a bilingual guidebook about Sendang Duwur Tourism Village that can be used by local and foreign tourists. The final result of this research was bilingual guidebook for Sendang Duwur Tourism Village in the electronic and printed version. The guidebook contains: general overview of the village with the history, the accessibility to the location, the tourist objects, the local products, the local delicacy, the events, cultural art, the accommodation, and tour package in 80 pages. The pictures of each site were also added to the guidebook to completing the content.